Business Intelligence Strategy for Company Business Development Using Online Analytical Processing - Rio Afrianda; Veithzal Rivai Zainal; Indra Siswanti (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
The purpose of this article is to discuss Business Intelligence and its role in increasing a company's competitive advantage through the utilization of various data, information and knowledge owned by a company as a raw material in the decision-making process. The method used in this article uses Online Analytical Processing. The results of the research are (1) data analysis has become a major and vital requirement in efforts to increase the business competitiveness of an organization or company; (2) entrepreneur-style decision making that tends to rely on intuition becomes less suitable in the midst of an increasingly competitive and complicated business environment; (3) BI is an e-business application that functions to convert data within the company (operational, transactional, and other data) into a form of knowledge; (4) BI emphasizes the implementation of the 5 utilization of information for the purposes of data sourcing, data analysis, situation awareness, risk analysis, and decision support.